Modeling the Effect of Changes in Solar Radiation Rays on Solar Cell Output Using MATLAB/Simulink - Ali Akbar Berutu; Ahmad Dani; Beni Satria (Sean Institute, 2025)
The intensity of solar radiation is the main factor that affects the performance of solar cells in generating electrical power. This study modeled the effect of solar radiation changes on the power output of solar panels using Matlab/Simulink, with solar radiation data from Nasa Power for the Tanjung Anom location. The simulation was carried out to measure the output power based on variations in solar radiation intensity and ambient temperature in the effective time range, namely 09.00 to 16.00. The results show that the intensity of solar radiation is directly proportional to the output power of solar panels. At the highest radiation intensity of 620.35 W/m², the maximum power produced reaches 107.6 W, with a voltage of 20.35 V and a current of 5.286 A. On the other hand, at the lowest radiation of 205.61 W/m², the power decreases to 11.94 W. The model successfully illustrates the linear relationship between solar radiation, voltage, current, and output power, and shows the sensitivity of solar panels to changes in environmental parameters. Using MATLAB/Simulink, this model can be used to design and optimize photovoltaic systems according to local conditions. This research makes an important contribution to a deep understanding of the characteristics of solar cells, as well as a reference in the development of more efficient and environmentally friendly solar energy systems.